Smart and Polite: Polite Language Skills Training for Students at SMP Negeri 2 Parepare: Smart dan Politeness: Pelatihan Kemahiran Berbahasa Santun bagi Siswa di SMP Negeri 2 Parepare - Lukman, Lukman; Indarwati, Indarwati; Haryeni, Haryeni; Safriadi, Safriadi; Meirling, Andi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This training aims to improve students' polite language skills at SMPN 2 Parepare. The problem encountered is that around 65% of students have difficulty in applying the principles of polite communication, both in interactions with teachers, peers, and in broader social contexts. The training program was developed by the Department of Indonesian Literature, Faculty of Cultural Sciences, Hasanuddin University, using Participatory Action Research and Culture-Based Learning approaches. The results of the training showed an increase in students' understanding and ability in polite language communication. The positive impact of this program can be seen in the changes in students' attitudes that show politeness in communication. In conclusion, this training is important to improve students' personal quality with polite language skills.